2018
DOI: 10.1016/j.metabol.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructure and cognitive decline in metabolic syndrome: a review of diffusion tensor imaging

Abstract: Metabolic syndrome is a cluster of cardiovascular risk factors defined by the presence of abdominal obesity, glucose intolerance, hypertension and/or dyslipidemia. It is a major public health epidemic worldwide, and a known risk factor for the development of cognitive dysfunction and dementia. Several studies have demonstrated a positive association between the presence of metabolic syndrome and worse cognitive outcomes, however, evidence of brain structure pathology is limited. Diffusion tensor imaging has of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
73
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 210 publications
7
73
1
1
Order By: Relevance
“…These results are consistent with previous studies showing that insulin resistance negatively affects brain function and structure within the hippocampus, dorsolateral prefrontal cortex as well as medial and temporal regions, which may contribute to cognitive impairment (49,50). There is also some evidence linking dyslipidemia and abnormal lipid metabolism with global and regional GM or WM atrophy or WM hyperintensities (13). Even if the specific contribution of each metabolic change cannot be established in the present study, our results suggest that improvements of glucose homeostasis and dyslipidemia following weight-loss might reverse the obesity-related WM and GM volume alterations.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results are consistent with previous studies showing that insulin resistance negatively affects brain function and structure within the hippocampus, dorsolateral prefrontal cortex as well as medial and temporal regions, which may contribute to cognitive impairment (49,50). There is also some evidence linking dyslipidemia and abnormal lipid metabolism with global and regional GM or WM atrophy or WM hyperintensities (13). Even if the specific contribution of each metabolic change cannot be established in the present study, our results suggest that improvements of glucose homeostasis and dyslipidemia following weight-loss might reverse the obesity-related WM and GM volume alterations.…”
Section: Discussionsupporting
confidence: 92%
“…Imaging studies in humans previously reported that obese individuals have reduced WM tissue density and altered WM integrity in dispersed tracts, including the corpus callosum, cingulum, cerebellar peduncle and corona radiata (9,12,13,17,19,29,43). These findings align well with our cross-sectional results showing that WM density in brain stem and cerebellar peduncle, two regions that significantly increased after SG, were reduced in severely obese individuals compared to normal-weight individuals.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations